Assessing The National Human Rights Commission's (Komnas Ham) Independence In Indonesia's Statement System - Ashar Hasanuddin (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2021)
The National Human Rights Commission (Komnas HAM) is an independent, national state commission tasked with the responsibility of conducting human rights studies, research, counseling, investigations, monitoring, and mediation. The purpose of this study is to ascertain Komnas HAM's status and role within the Indonesian Constitutional System, as well as its accountability within the Indonesian Constitutional System. According to the nature of the inquiry, this is a library research on the subject of Komnas HAM. The syar'i theological approach was applied in the investigation. The findings of this study reveal that Komnas HAM has a distinct status and function within the Indonesian constitutional system; Komnas HAM's job is to strengthen human rights protection and enforcement. The research's implications are to emphasize Komnas HAM's constitutional status in Indonesia and to realize human rights enforcement through Komnas HAM's partnership with the community. Keywords: Komnas HAM; Siyasah Syar’iyyah; Wazir al-tawfid